Thirty-five years of peer-reviewed publishing by north American economics PhDs: Quantity, quality, and beyond - Ali Sina Önder; Hakan Yilmazkuday (Open Economics, 2020)
We provide a descriptive analysis of various qualities of peer-reviewed journal publications of graduates of North American economics PhD programs between 1980 and 2014. We find that the share of single-author papers in all published papers diminishes from 60% in 1980 to 50% in 1990 and then further down to 20% in 2014. All-female and mixed-gender author teams publish significantly less compared with all-male author teams between 1980 and 1999, but we find no significant difference after 2000. While male authors are over-represented in micro and macroeconomics, female authors are over-represented in labor and development economics. Although the quality of outlets for most fields does not change much over years, labor economics and economic history are published significantly better after 2000.
Keywords: A11; A14; 330; Economics PhD; Research Activity; Co-authorship; Subfields of Economics; Gender